The readiness of mathematics teachers as agents of change: a recent comprehensive review - Abu Talib, Sharida; Mohamad Nasri, Nurfaradilla; Mahmud, Muhammad Sofwan (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study scrutinizes the role of mathematics teachers as pivotal agents of change in the evolving educational landscape, focusing on their readiness to embrace pedagogical reforms. The review aims to reveal the current patterns and trends in mathematics teachers’ readiness literature discussed in recent studies. Utilizing the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, this study analyzed 31 empirical articles from the Scopus and Web of Science databases in 2023. The review process for chosen articles is examined, encompassing aspects such as publication criteria, eligibility and exclusion standards, databases, and the progression of review stages. The most striking result from the analysis is that mathematics teachers’ readiness is closely related to teaching strategies and pedagogy. Moreover, inconsistencies in practice and constraints such as inadequate resources, insufficient institutional support, and teacher training program gaps hinder their ability to implement change effectively. The implications of this study extend to various stakeholders in the education ecosystem, including policymakers, educational institutions, teacher training programs, and practitioners. This review suggests strategies to enhance teachers’ professional development and serve as preliminary work toward developing a pedagogy model. In conclusion, this systematic review consolidates the existing knowledge on the readiness of mathematics teachers as agents of change.